PHYTOTOXICITY ASSESSMENT OF CYPERUS DIFFORMIS (L.) TOWARDS A SUSTAINABLE WEED MANAGEMENT OPTION - M. S. Islam; H. Kato-Noguchi (Journal of Animal and Plant Sciences, 2016)
The present study was conducted to evaluate the allelopathic potentiality of Cyperus difformisfrom the Cyperaceae family. Aqueous methanol extracts from C. difformis were applied at four concentrations (0.01, 0.03, 0.1 and 0.3 g dry weight [DW] equivalent extract/mL) on the seedling growth of eight test species namely, cress (Lepidum sativum L.), lettuce (Lactuca sativa L.), alfalfa (Medicago sativa L.), rapeseed (Brassica napus L.), Italian ryegrass, (Lolium multiflorum Lam.), barnyard grass (Echinochloa crus-galli L.), timothy (Phleum pratense L.) and sand fescue (Festuca megalura Nutt.). A complete inhibition of seedlings of lettuce was found at concentration of 0.1 g DW equivalent extract/mL.At a concentration of 0.3 g DW equivalent extract/mL, complete inhibition was also found in cress shoot and root of cress, alfalfa, timothy and sand fescue, whereas others test species showed more than 90% inhibition. This inhibition was concentrations dependent and increased with increasing extracts concentrations. Considering concentrations required for 50% growth inhibition (I50), rapeseed was the most sensitive to the extracts.The results indicate that, C. difformismay possess allelopathic properties and therefore, could be a candidate for the isolation and identification of allelopathic substances to develop environment friendly bio-herbicides.
Keywords: allelopathy and allelochemicals; Cyperus difformis; aqueous methanol; I50; bio-herbicides